Optimalisasi Penggunaan Artificial Intelligence untuk Mendukung Pembelajaran Matematika di SMA - Sri Rejeki; Rini Setyaningsih; Christina Kartika Sari; Adi Nurcahyo (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Technological literacy among high school mathematics teachers is a crucial aspect in realizing creative, interactive, and relevant learning to meet the demands of the 21st century. However, the reality on the ground shows that most mathematics teachers still have limited experience in improving technological literacy, particularly in the use of artificial intelligence (AI) as a learning support medium. This condition has implications for low innovation in the mathematics learning process. This community service activity aims to optimize the use of AI, specifically Generative-AI technology, in supporting mathematics learning in high schools. The target group is members of the High School Mathematics Subject Teachers' Conference (MGMP) throughout Grobogan Regency, Central Java Province, Indonesia. The implementation method includes workshops, interactive discussions, hands-on practice, and mentoring in the development of AI-based mathematics teaching materials, assessments, and learning media. The training materials include an introduction to the basic concepts of Generative-AI, effective prompting techniques, and practice using various AI applications to produce interactive and contextual teaching materials. Evaluation results showed that all training participants agreed or strongly agreed that this activity successfully improved their understanding of the basic concepts of Generative AI and their skills in operating AI applications for mathematics learning. Participants also reported increased confidence in integrating AI technology into their teaching practices, as well as gaining various relevant practical ideas for classroom implementation. High enthusiasm was evident in the 100% commitment of participants who expressed their readiness to implement AI technology in mathematics learning. Thus, this training not only contributed to improving teachers' technological literacy but also became a strategic step in encouraging innovative and adaptive transformation of mathematics learning in the digital era.